Chemical constituents of Cryptocarya densiflora / Wan Nurul Nazneem binti Wan Othman - Wan Othman, Nurul Nazneem (2010)
The extraction of alkaloids from the Malaysian Cryptocarya densiflora has been carried out in this study. The alkaloids were extracted from the bark and leaves of this species using acid base extraction and the crude alkaloids obtained were subjected to extensive chromatographic techniques such as thin layer and column chromatography. The structural elucidation of the purified alkaloids were performed with the aid of spectroscopic methods i.e. 1H NMR, 13C NMR, 2D NMR, IR, UV and LCMS. Investigation of the alkaloidal content from the bark of Cryptocarya densiflora afforded six alkaloids and their structures were elucidated as laurotetanine 63, isocaryachine 64, N-demethylphyllocryptine 65, nornantenine 66, reticuline 14 and laudanidine 2. Isolation and purification of alkaloids from the leaves of Cryptocarya densiflora afforded four alkaloids of which one is novel compound: cryptocaryadine 68 along with three known compounds: dicentrinone 67, crychine 60 and N-methyllaurotetanine 53.